Las Actas de los mártires. Una actualización de los Documentos Sobre los Primeros Cristianos - Mateo Donet, Maria Amparo (Augustinianum, 2014)
This paper is an update of the documents we have concerning the Acts of the Christian martyrs, focused on three main aspects: 1) the kind of acts we know of and their classification from the point of view of their historic value; 2) the versions or editions of the texts that are most accepted by scholars; 3) the relevance of the different parts that make up these documents in order to discern the original text from passages that were rewritten or underwent later variations. In this way, the article offers an exhaustive list of the documents for use in researching Christian martyrs in the Roman period.